Ethical Leadership Effect Trust in Leader, Work Engagement and Burnout Over Turnover Intension - Dany Prastio; Rhian Indradewa; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2020)
This study aims to analyze the effect of ethical leadership on trust in leader, to analyze the influence of trust in leader on work engagement, to analyze effect of work engagement on turnover intension, to analyze the influence of ethical leadership on burnout and to analyze the influence of burnout on turnover intension of ICT employees. The population used in this study are all distributors or other business companies that are employees of ICT Company which number 375 employees. While the sample of this study was 30 respondents who were considered to have adequately represented the population studied. The sampling technique uses the Convenience Sampling method, which is a sampling method based on the convenience factor where the respondents happened to meet with the research at the survey location. The analytical model used in this study is descriptive analysis and analysis of Structural Equation Modeling with the Lisrel Program. The results of the study found that found that: 1) Trust in leaders is influenced by ethical leadership. The better and higher the ethical leadership, the better the trust in leader. 2) Work engagement is not influenced by employee's trust in leaders. This might occur in the ICT industry, where there are other factors that can affect employee's work engagement. 3) Turnover intention is not influenced by work engagement. If the value of work engagement is high, the less likely the employee will be to leave the company. 4) Ethical leadership is negatively related to burnout. If the ethical leadership value is low, then the higher the burnout. 5) Turnover intension is influenced by burnout. This shows that the higher the burnout, the higher the likelihood that employees will leave the company